Gene transfer system for the phytopathogenic fungus Ustilago maydis. - Wang, J (1988)
A selectable marker for transformation was constructed by transcriptional fusion of a Ustilago maydis heat shock gene promoter with the hygromycin B phosphotransferase gene of Escherichia coli. U. maydis was transformed to hygromycin B resistance by polyethylene glycol-induced fusion of spheroplasts following exposure to plasmid DNA that carried the marker gene. Transformation frequencies of 50 and 1000 transformants per microgram of DNA per 2 x 10(7) spheroplasts were obtained for circular and linear vector DNA, respectively. In the majority of transformants, the vector was integrated at a single chromosomal site, in either single copy or tandem duplication, as determined by Southern hybridization analysis of electrophoretically separated chromosomes and of restriction-endonuclease-cleaved DNA. The predominant form (82%) of vector integration was by nonhomologous recombination; the remainder carried the plasmid at the homologous heat shock gene locus. No evidence for gene conversion or gene replacement was obtained in 28 transformants. Hygromycin B phosphotransferase activity and resistance to hygromycin B were roughly correlated with the copy number of the integrated vector at the homologous location. Transforming DNA was stably maintained during mitosis and meiosis. This transformation procedure and associated vector should permit the cloning of genes by direct complementation in U. maydis.